2018
DOI: 10.1111/aogs.13504
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion following intended vaginal birth after cesarean vs elective repeat cesarean section in women with a prior primary cesarean: A population‐based record linkage study

Abstract: Introduction:There is a lack of evidence around the risk of transfusion following vaginal birth after cesarean (VBAC) compared with elective repeat cesarean section (ERCS); this is important for decision-making about birth options. The aim of this study was to determine transfusion rates and risk of transfusion following intended VBAC and ERCS. Material and methods: Women with a primary cesarean who had a subsequent birth at term (≥37 weeks) in New South Wales between 2000 and 2012, were identified from the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…In a retrospective study of patients undergoing blood transfusion after cesarean section, Abbas et al pointed out that the main causes of blood transfusion are uterine weakness, scarred uterus, placental adhesion, placenta accreta, prenatal anemia, placenta previa, and so on [ 17 ]. Pont et al found that the increase of blood transfusion rate during cesarean section after the opening of the comprehensive “two-child policy,” ASA grade III-IV, operation time longer than 60 min, and preoperative complications were independent risk factors for blood transfusion during cesarean section [ 18 ]. He et al proposed that placenta previa is the primary risk factor for intraoperative blood transfusion for second cesarean section, and women with placenta previa have a higher probability of intraoperative blood transfusion [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of patients undergoing blood transfusion after cesarean section, Abbas et al pointed out that the main causes of blood transfusion are uterine weakness, scarred uterus, placental adhesion, placenta accreta, prenatal anemia, placenta previa, and so on [ 17 ]. Pont et al found that the increase of blood transfusion rate during cesarean section after the opening of the comprehensive “two-child policy,” ASA grade III-IV, operation time longer than 60 min, and preoperative complications were independent risk factors for blood transfusion during cesarean section [ 18 ]. He et al proposed that placenta previa is the primary risk factor for intraoperative blood transfusion for second cesarean section, and women with placenta previa have a higher probability of intraoperative blood transfusion [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Pont et al ( 16 ), the authors concluded that the risk of transfusion was higher for women attempting vaginal birth after a primary CS than after a planned repeat Cesarean. In our study, the necessary of blood transfusion was small, and was required in two cases of VBAC with vacuum extraction that had cervical tears.…”
Section: Discussionmentioning
confidence: 99%
“…1 They performed a retrospective population-based record linkage study evaluating the transfusion risk associated with intended vaginal birth after cesarean (VBAC) compared to elective repeat cesarean section (ERCS). 1 They performed a retrospective population-based record linkage study evaluating the transfusion risk associated with intended vaginal birth after cesarean (VBAC) compared to elective repeat cesarean section (ERCS).…”
Section: Postpartum Hemorrhage and Blood Transfusion Among Parturientmentioning
confidence: 99%
“…We read the study by Pont et al with great interest. 1 They performed a retrospective population-based record linkage study evaluating the transfusion risk associated with intended vaginal birth after cesarean (VBAC) compared to elective repeat cesarean section (ERCS).…”
Section: Postpartum Hemorrhage and Blood Transfusion Among Parturientmentioning
confidence: 99%